HLA-DR3 and DR7 in coeliac disease: immunogenetic and clinical aspects. Issue 8 (August 1983) - Demarchi, M; Carbonara, A; Ansaldi, N; Santini, B; Barbera, C; Borelli, I; Rossino, P; Rendine, S
Abstract : The association of HLA-A, B, C, DR polymorphisms and of Bf and GLO with coeliac disease was analysed in 100 Italian children. Primary involvement of HLA-DR3 and DR7 is apparent, while specificities of nearby loci are probably associated secondarily, because of linkage disequilibrium. Direct assessment of D/DR genotype through family studies and mixed lymphocyte cultures led to the recognition of two high risk genotypes DR3/3 and DR3/7, and of two lower risk genotypes DR3/X and DR7/X. The different weight of the HLA-dependent genetic factors is to some extent correlated with the clinical and immunological parameters, suggesting that the low-risk genotypes induce a milder expression of coeliac disease. Furthermore, other genetic factors, such as sex, appear to contribute to the penetrance of the disease, especially in the case of DR3/X and DR7/X.